A Brief Research on ICP-OES Determination of Trace Metals in Groundwater of Proddatur Area, YSR Kadapa Dist., Andhra Pradesh, India - Pulapaka, Suresh; Shaik, Beebi (Chemistry and Biochemistry: Research Progress Vol. 5, 2025)
Water is among the most valuable resources on the planet, as it is required for life's existence and sustenance. Groundwater is the only drinking water source in the study area. Heavy metals may be considered as contaminants in the groundwater of this area due to the dyeing and electroplating industries. Extreme amounts of heavy metals within drinkable waters may have a variety of short- and long-term health consequences for humans. There are no reports of heavy metals in any previous studies of this area. Ten groundwater samples were collected from different locations of Proddatur and analyzed for twelve trace metals, namely arsenic, cadmium, manganese, copper, iron, mercury, chromium, nickel, lead, molybdenum, zinc, and selenium, using the Inductively Coupled Plasma- Optical Emission Spectrometry (ICP-OES) method at trace levels. The proportion of elements in the examined sample determines the strength of the energy released. The results showed that 70% of samples contained Molybdenum, 30% of samples contained lead and copper which were reported within allowable bounds of the World Health Organization (WHO). The cadmium concentration in 40% samples was detected above the WHO guidelines. Cadmium is a very hazardous environmental and industrial waste adulterant. Consumable water containing high amounts of cadmium causes severe stomach irritation, resulting in vomiting, diarrhea, renal damage, osteoporosis, & osteomalacia. So, periodical monitoring and an elaborate study on heavy metal pollution in groundwater are suggested. In conclusion, as Cadmium concentrations were found to be over the WHO permitted limit in 40% of the research area's samples, it is recommended that the polluted sources of concern undergo further treatment to minimize the concentration of this detected trace metal, which might pose a health risk. Trace metal levels should be checked on a regular basis using proactive techniques.